PENGEMBANGAN KURIKULUM PENDIDIKAN KRISTIANI - Branckly Egbert Picanussa (Voice of Wesley: Jurnal Ilmiah Musik dan Agama, 2020)
Some Christian education experts have expressed their views on how the church should develop a curriculum to educate church members to achieve maturity in the Christian faith. This article purpose to develop a curriculum for Christian education in Church ministry. The method used is a literature study on the opinions of D. CampbellWyckoff and Maria Harris. The characteristics of Wyckoff and Harris's opinions and various responses in "imaginative dialogue", as well as modifications of the Christian education Foundations, Principles andPractices schemes of Robert W. Pazmino became a model to develop a Christian education curriculum in church life. The development of the Christian education curriculum begins with setting the goal of implementing Christian education for a group in the Christian community. Furthermore, curriculum development requires thecontribution of various development foundations, including biblical, theological, philosophical, educational, scientific and technological, historical, socio-cultural, ecclesiological and psychological.